There is Always an Alternative: A Study of Control and Commitment in Political Organization - Emil Husted (Copenhagen Business School (CBS), 2017)
This doctoral study explores the case of The Alternative, a recently elected party in Denmark, by utilizing concepts and methods from organization studies in an effort to understand how a political party manages the process of entering parliament without losing political support. The Alternative was founded in late 2013 as a movement against the unsustainable program of neoliberal capitalism and the `old political culture'. However, instead of presenting a list of tangible demands and trademark issues, The Alternative was launches without a political program. During the course of only half a year, the party developed its political program with inspiration from the open-source community by inviting everyone interested to participate in a series of `Political Laboratories'. This culminated with the publication of The Alternative's first program in May 2014 – a document of no less than 63 pages, containing a variety of specific and sometimes controversial policy proposals. On June 18, 2015, the party entered the Danish Parliament with almost five percent of the votes.
hdl:10398/9534
Keywords: 650